A Novel One‐Day Learning Procedure for Mice. Issue 1 (25th February 2020) - Darvas, Martin; Mukherjee, Kishore; Lee, Amanda; Ladiges, Warren
Abstract: Current preclinical cognitive assessments are highly time intensive, with lengthy assessment procedures. In this regard, a single‐day assay that focuses just on assessing learning behavior in a time‐effective and relatable manner would be of value. This article describes the box maze as a short‐term behavioral procedure to measure learning in mice. The protocol consists of allowing mice to explore an enclosed space that has eight holes. One of these holes leads to a tunnel that connects to an escape cage, and the latency to enter this escape hole is recorded for each mouse. Mice are tested four times within a single day, and the decrease in escape latency over time is used as a measure of learning. Age is a factor that affects escape latency in the box maze. Hence, the box‐maze procedure is proposed as an efficient test to probe aging and aging intervention–related research questions. © 2020 by John Wiley & Sons, Inc.